2007
DOI: 10.1101/gr.6427907
|View full text |Cite
|
Sign up to set email alerts
|

Whole proteome analysis of post-translational modifications: Applications of mass-spectrometry for proteogenomic annotation

Abstract: While bacterial genome annotations have significantly improved in recent years, techniques for bacterial proteome annotation (including post-translational chemical modifications, signal peptides, proteolytic events, etc.) are still in their infancy. At the same time, the number of sequenced bacterial genomes is rising sharply, far outpacing our ability to validate the predicted genes, let alone annotate bacterial proteomes. In this study, we use tandem mass spectrometry (MS/MS) to annotate the proteome of Shew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
225
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(238 citation statements)
references
References 97 publications
7
225
1
5
Order By: Relevance
“…A number of pipelines have successfully exploited high-throughput tandem mass-spectrometry (MS/MS) data to predict novel proteins in H. sapiens (Fermin et al 2006;Tanner et al 2007;Bitton et al 2010), Caenorhabditis elegans (Schrimpf et al 2009), Drosophila melanogaster (Schrimpf et al 2009), Arabidopsis thaliana (Castellana et al 2008), and bacteria (Gupta et al 2007). We have therefore applied a pipeline that integrates this proteogenomics approach (Bitton et al 2010) with comparative genomics and genomewide domain prediction to augment the current annotation of S. pombe.…”
Section: T He Fission Yeast Schizosaccharomyces Pombe Is a Widelymentioning
confidence: 99%
“…A number of pipelines have successfully exploited high-throughput tandem mass-spectrometry (MS/MS) data to predict novel proteins in H. sapiens (Fermin et al 2006;Tanner et al 2007;Bitton et al 2010), Caenorhabditis elegans (Schrimpf et al 2009), Drosophila melanogaster (Schrimpf et al 2009), Arabidopsis thaliana (Castellana et al 2008), and bacteria (Gupta et al 2007). We have therefore applied a pipeline that integrates this proteogenomics approach (Bitton et al 2010) with comparative genomics and genomewide domain prediction to augment the current annotation of S. pombe.…”
Section: T He Fission Yeast Schizosaccharomyces Pombe Is a Widelymentioning
confidence: 99%
“…Using these datasets, 24 Mascot MS/MS Ion searches, including decoy database searches, were conducted to 25 identify potential PTMs in D. vulgaris. Recently, a number of similar studies have been 26 reported in other organisms [12][13][14] . Many PTMs are known to play critical roles in bacterial 27 regulation.…”
Section: Introductionmentioning
confidence: 66%
“…In this search, a total of 6220 unique peptide 13 sequences passed the filtering thresholds. Of these, 309 (~5%) were identified as having 14 an unlabeled peptide N-terminus. A total of 2665 sequences contained one or more 15 lysines, and of these, only 14 (~0.5%) were identified as having unlabeled K. The overall 16 trend observed is that iTRAQ labeling is highly efficient for K side chains, but peptide N-17 termini are slightly less reactive.…”
Section: Methods 28mentioning
confidence: 99%
“…Moreover, the same experimental proteomic datasets are also useful in identifying PTMs on a proteome wide level [100,101]. Our group developed a proteogenomic approach to carry out genome annotation and whole-proteome analysis of PTMs in prokaryotes by employing high resolution and high accuracy MS data, and we used this approach to study the global PTMs in the model cyanobacterium Synechococcus 7002 [27].…”
Section: Global Discovery Of Ptmsmentioning
confidence: 99%